2023
DOI: 10.1002/anie.202310234
|View full text |Cite
|
Sign up to set email alerts
|

Thermally‐Induced Isomerization of Prenucleation Clusters During the Prenucleation Stage of CdTe Quantum Dots

Abstract: The evolution of prenucleation clusters in the prenucleation stage of colloidal semiconductor quantum dots (QDs) has remained unexplored. With CdTe as a model system, we show that substances form and isomerize prior to the nucleation and growth of QDs. Called precursor compounds (PCs), the prenucleation clusters are relatively optically transparent and can transform to absorbing magic‐size clusters (MSCs). When a prenucleation‐stage sample at 25, 45, or 80 °C is dispersed in a mixture of cyclohexane (CH) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…A fundamental understanding of the initial formation of the prenucleation clusters, PC-371, and the transformation to dPC-485 in the reaction can be found elsewhere (Figure S1C). , As shown in Figure S1–4, a 135 °C/60 min sample contained dMSC-485 and QD-580 (a). For the mixture, TEM suggested an average size of ∼3.4 nm (b), X-ray diffraction (XRD) showed a structure that is more zinc blende-like rather than wurtzite-like (c), and energy dispersive X-ray spectroscopy (EDX) and scanning electron microscopy (SEM) showed the 1.1Cd to 1.0Te number ratio (d).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A fundamental understanding of the initial formation of the prenucleation clusters, PC-371, and the transformation to dPC-485 in the reaction can be found elsewhere (Figure S1C). , As shown in Figure S1–4, a 135 °C/60 min sample contained dMSC-485 and QD-580 (a). For the mixture, TEM suggested an average size of ∼3.4 nm (b), X-ray diffraction (XRD) showed a structure that is more zinc blende-like rather than wurtzite-like (c), and energy dispersive X-ray spectroscopy (EDX) and scanning electron microscopy (SEM) showed the 1.1Cd to 1.0Te number ratio (d).…”
Section: Resultsmentioning
confidence: 99%
“…20−27,30−36,38−41 Meanwhile, the PC-to-PC transformations in reactions have been elaborated elsewhere (Figure S1C). 24,25 The prenucleation stage of CdTe QDs, for example, can be as long as 20 min at a constant temperature of 135 °C for a reaction in oleylamine (OLA, CH 3 (CH 2 ) 7 −CH�CH− (CH 2 ) 8 −NH 2 ) of Cd(OAc) 2 /OLA (made from cadmium acetate and OLA) and TeTOP. 20−23 When a prenucleationstage sample (which was preheated at 135 °C for ∼20 min) was dispersed in a mixture of toluene (Tol) and a primary amine octylamine (CH 3 (CH 2 ) 7 −NH 2 , OTA) at room temperature, CdTe MSC-371 (displaying sharp optical absorption singlet peaking at ∼371 nm) was seen (Part a of Figure S1B).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, a complete anion exchange process in CdSe, CdS, and CdTe MSCs was achieved for the first time under mild conditions, and the intrinsic transformation mechanism was systematically investigated. We proposed that covalent inorganic complexes (CICs) played a critical role as intermediates in the intermolecular transition of template-free MSCs (nonstoichiometric composition), which was distinct from the intramolecular anion exchange process found in templated MSCs (stoichiometric composition). , An in situ absorption spectroscopy study showed that the conversion pathway from CdE 1 -MSCs to CdE 2 -MSCs (Scheme ) involved three key steps, namely the disassembly of CdE 1 -MSCs into CdE 1 -CICs (step 1, eq ), the anion exchange reaction that transformed CdE 1 -CICs into CdE 2 -CICs (step 2, eq ), and the assembly of CdE 2 -CICs into CdE 2 -MSCs (step 3, eq ). Steps 1 and 2 were relatively fast, and step 3 was a rate-determining step, following the behavior of first-order reaction kinetics with a rate constant ( k 1 ) of 0.01 min –1 ( t 1/2 of 69.3 min), which was five times faster than the rate constant of the anion exchange reaction in templated MSCs.…”
Section: Introductionmentioning
confidence: 99%